2021
DOI: 10.1371/journal.pone.0256313
|View full text |Cite
|
Sign up to set email alerts
|

Tempo-spatial variations of zooplankton communities in relation to environmental factors and the ecological implications: A case study in the hinterland of the Three Gorges Reservoir area, China

Abstract: To expand the knowledge on the tempo-spatial patterns of zooplankton and the key modulated factors in urban aquatic ecosystem, we investigated zooplankton and water quality from April 2018 to January 2019 in the hinterland of the Three Gorges Reservoir area, Wanzhou City of China. The results indicated that water quality indicated by the trophic state index (TSI) reached a state of mesotrophication to light eutrophication in the Yangtze River, and a state of moderate- to hyper- eutrophication in its tributarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…This may have arisen from similar environmental parameters that lead to similar selection pressures 72 . Indeed, a recent study found the occurrence of B. diversicornis to be correlated with warmer water temperatures 73 , which could indicate a higher thermotolerance—as observed in B. calyciflorus s.s. 35 , 36 —also in this species.…”
Section: Discussionmentioning
confidence: 96%
“…This may have arisen from similar environmental parameters that lead to similar selection pressures 72 . Indeed, a recent study found the occurrence of B. diversicornis to be correlated with warmer water temperatures 73 , which could indicate a higher thermotolerance—as observed in B. calyciflorus s.s. 35 , 36 —also in this species.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, the similarity in HSP 40KDa gene sequences among the not directly related species B. diversicornis and B. calyci orus s.s. may have arisen from similar environmental parameters that lead to similar selection pressures (Turner et al, 2018). Indeed, a study by Lan et al (2021) found the occurrence of B. diversicornis to be correlated with warmer water temperatures, which could indicate a higher thermotolerance -as observed in B. calyci orus s.s. (Paraskevopoulou et al 2018(Paraskevopoulou et al , 2020) -also in this species.…”
Section: Genetic Variation In the Hsp 40kda Gene Among Brachionus Spe...mentioning
confidence: 98%